KEEFEKTIFAN MEDIA ASOSIASI GAMBAR DALAM PEMBELAJARAN MENULIS HURUF HIRAGANA PADA SISWA KELAS VII SMP YLPI MARPOYAN PEKANBARU - Winda Friska Leoni; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: This research discusses about by using Image Association Media in hiragana writing learning students of YLPI Junior High School Marpoyan Pekanbaru. The purpose of this research is to knowing the effectiveness by using Image Associations Media and differences in student learning outcomes between classes that using Image Association Media with classes that did not using Image Association Media. The object of the research is class VII students of YLPI Junior High School Marpoyan in the odd semester academic year 2018/2019 was consisting of two classes, the class name is class VII.1 and class VII.2. This research used a pretest-posttest design, which was conducted on two classes namely the experimental class and the control class. The results of the research is was found that the Image Association Media could improve students outcomes learning in hiragana writing learning compared the results of the students outcomes learning in hiragana writing learning by used conventional methods. This can be seen from the evaluation value and the difference in the results of the experimental class pretest and posttest (the treated class) increased, is 80.8 for the average value in the experimental class and 69 for the control class.Key Words: Effectiveness, Association Hiragana.